Planting Design Approach in Sustainable Urban Planning (International Journal of Built Environment and Sustainability, 2021)
The increased pressures associated with climate change and urbanization processes adversely affect the quality of life of the cities and damage the sustainability of the cities. Sustainability of a city depends on the social, economic and ecological flexible uses that these pressures can tolerate. The examination of these flexible uses within the city brings along the sustainability of the landscape. Landscape serving flexible uses for urban sustainability; All the unconscious elements that make up that landscape, especially the vegetation landscape element, should support the concept of sustainability. Within the scope of the study, it was aimed to determine sustainable design approaches in the fields of planting and to create an evaluation scale accordingly by examining the sustainable planting design approaches in urban scale. An answer was sought to the question of how sustainable the planting activities of Trabzon province are. In the study, 40 studies defined as sustainable landscape areas were examined and 27 sub-parameters were developed under 4 main titles within the framework of these studies. The parameters are examined in the regions represented by the city components that make up the city and it is tried to determine what is necessary for the sustainability of the city
Keywords: Sustainable Planting Design; Sustainable Planting; Sustainable Cities; Urban Planning; Trabzon